The possibilities of day surgery system development within the health policy in Slovakia - Vincent Šoltés; Beáta Gavurová (Health Economics Review, 2014)
Background: In the day surgery system are intertwined elements of state health policy, health care payers' interests, employers of health care system, as well as the interests and wishes of patients. A problem in the health policy is to find a way to regulate ambulatory and short-term surgical procedures, which are hardly distinguishable, and still fulfil the requirements of transparent financing, quality and security. The objective of this paper is to highlight the reasons for the long-term stagnation in Slovakia day surgery and the possibilities of eliminating the structural drivers causing this negative phenomenon. Methods: Due to the nature of the analyzed data and desired outcomes, we selected application of correspondence analysis. Results of correspondence analysis provide valuable information necessary for the projection of specialization of one day surgery clinics for that type of procedure, as well as for the support of the new clinics creation (also with the potential state support), the pricing policy, systemic reduction of beds what is connected with reduction of underutilized departments in hospitals, in order to optimize management processes in the healthcare system. Results: Contribution reveals negative aspects which causing a low level of day surgery in Slovakia. Moreover, it reveals the approaches of the different subjects of day surgery. Presented options for setting optimal strategy supporting its development are based on the results of the analysis. Correspondence analysis provided valuable information of present structure of the day surgery system. The determined similarity of the regions and association of specialized fields indicate specific settings of the day surgery system and its components that are inevitable to analyze in the subsequent analytical process. Conclusions: Results of the analysis are very important in order to set up the system measures in the process of its further development, which should be part of the strategic plan of each health system. On conceptual and methodological issues related with reporting of day surgery performances are highlighting international organizations such as the OECD,WHO.
Keywords: I13; I18; H51; 330; Health policy; Health financing policy; System of one-day surgery; Efficiency of health care; Correspondence analysis; Methodological problems of reporting